2011
DOI: 10.1177/1538192711402690
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors of a Web-Based Seminar That Influence Hispanic Preservice Teachers’ Critical Thinking and Problem-Solving Skills

Abstract: The purpose of the qualitative study using a phenomenological approach was to gain insight of preservice teachers' experiences with a WebCT seminar designed to develop critical thinking and problem-solving skills in a Hispanic-Serving Institution's teacher education program. By applying a "holistic approach" to analyze data, NVivo software was used to assist the process. Findings indicate the use of discussion board and a reading strategy were influential in developing critical thinking and problemsolving skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Pre-service teachers who do not adopt these skills during their educational lives feel themselves inadequate when they start to educate students. In their studies, Garcia and Hooper (2011), revealed that teachers do not really know how to cultivate thinking skills in students.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…Pre-service teachers who do not adopt these skills during their educational lives feel themselves inadequate when they start to educate students. In their studies, Garcia and Hooper (2011), revealed that teachers do not really know how to cultivate thinking skills in students.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…In problem-based learning four researchers began to experiment with wikis and forums, unguided group research, multimedia, web 2.0 tools, and the use of second life (Beaumont, Savin-Baden, Conradi, & Poulton, 2014;Ioannou, Brown, & Artino, 2015;Liu et al, 2014;Walker, 2014). In critical thinking, five recent articles were found where researchers explored web-based seminars, web 20 tools and mobile learning in nurse's education, web-based graduate management courses, and wikis (Condon & Valverde, 2014;Eales-Reynolds, Gillham, Grech, Clarke, & Cornell, 2012;Garcia & Hooper, Jr., 2011;Goh, 2012;Lai & Wu, 2012). It is evident that problem-based learning in online (or web-based) environment is the most recent subject to be addressed and interest in general seems to be increasing.…”
Section: Resultsmentioning
confidence: 99%
“…Survei dikirimkan melalui email ke para responden dan dilakukan melalui aplikasi google form http://bit.ly/EvaluasiWebinarDJP2020. Dari berbagai penelitian sebelumnya ditemukan bahwa webinar konsisten menunjukkan adanya "pertukaran virtual" yang memuat diskusi nyata secara daring (Garcia & Hooper, 2011). Bahkan Schwier & Winn (sebagaimana dikutip oleh Teng et al, 2012) menjelaskan webinar dirancang dan diatur untuk memberikan pengantar Tabel 1 Sampling Frame Peserta Webinar DJP Sumber: DJP Periode Juni-September 2020 teori, praktik, dan diskusi di dalam ruang publik.…”
Section: Metodologi Penelitian 31 Metode Penelitianunclassified